A Pasture Of Big Ungulate Animals As Key Ecological Factor Influencing On The Fluctuation Of Natural Habitat Of Steppe Herbivorous Mammals - Tokarsky, V (Zoodiversity (Online), 2015)
The objective laws of the natural habitat structure of European subspecies of the steppe marmot over the period of the 20-21st centuries in Rostov Region have been analyzed. Essential changes in the way of usage of nature and foremost the decrease of number of stock-raising capacities and pasture areas took place all over the territory of European subspecies of the steppe marmot natural habitat. There is no doubt that the agricultural usage of land contributed to the inhabitance of big quantity of steppe marmots, namely keeping big quantities of horses and cattle which had large territories used as pasture areas. During these periods, we can see the substantial decreases of the steppe marmot's population despite full prohibition of hunt (since 1929 there has been no industrial hunting for steppe marmots). In first case, over a 30-year period, the steppe marmots completely disappeared from the territory of Rostov Region. The second period is not over yet. Here we can foresee two variants of the situation development. At present the period of the steppe marmot disappearance has reached its midpoint. If the quantity of cattle and horses remains the same we can surely make forecasts of continued decrease of marmot's population. However, if a cattle breeding increases the population of steppe marmots will be able to restore its natural habitat to previous size.